Planejamento financeiro para gestão: estudo de caso em uma empresa agrícola - Fachi, Giséli Bueno (2024)
Financial planning is a way in which the administrator can carry out an analysis of the desired period and plan with greater precision for future moments. For the sector rural, this tool has low demand and service supply, as it is not highlighted, this work seeks to highlight the real importance of this procedure through the search for data of a company in the rural sector, future estimates, cash flow development and analysis of the obtained result. It was based on quotes and concepts from works related to the topic is approached through the qualitative method with explanatory objectives, in a study of case of a specific company in the sector. The values ​​in the flow of direct method box and analyzed all accounts of inflows and outflows of resources and projected with changes based on the subsequent period. Arriving at the result that the expectation be it an improvement in the operational financial situation, with greater productivity and lower costs in relation to previous periods, with an increase of R$ 3,922,061.99, or 72% in its availability until the end of the stipulated period, even if it takes a few months to have this return.